Experts' views on the implementation of digital interventions for eating disorders: a Delphi study - Diana Lemmer; Gwendolyn Mayer; Pauline Schrader; Ina Michelsen; Hans-Christoph Friederich; Stephanie Bauer (BMC, 2024)
Abstract Background Eating disorders (EDs) constitute a considerable burden for individuals and society, but adequate and timely professional treatment is rare. Evidence-based Digital Mental Health Interventions (DMHIs) have the potential both to reduce this treatment gap and to increase treatment effectiveness. However, their integration into routine care is lacking. Understanding practitioners' attitudes towards DMHIs for EDs is crucial for their effective use. Aims To investigate the consensus among German ED treatment experts on the relevance of different influencing factors for DMHI use in EDs. Methods This Delphi study consisted of two rounds and was conducted online with an initial sample of N = 24 ED experts (M age=41.96, SD age=9.92, n = 22 female). Prior to the Delphi rounds, semi-structured qualitative telephone interviews were performed to explore participants' attitudes, experiences, and expectations towards DMHIs. In order to construct the Delphi survey, content analysis was applied to a subset of ten interviews. A total of 63 influencing factors were identified and grouped into three main categories: contextual conditions, design, and content of DMHIs. In both Delphi rounds, the interview participants were subsequently invited to rate each of the factors with regard to their importance on 10-point scales. Group percentages and individual ratings of the first round (n = 23) were presented in the second round (n = 21). Consensus was calculated for each item (defined as IQR ≤ 2). Results Importance ratings were high across items (M = 7.88, SD = 2.07, Mdn = 8). In the first round, 48% of the items reached consensus, with its most important (Mdn = 10) factors referring to data security, evidence base, technical requirements, usability, and specific DMHI content (psychoeducation, crisis intervention). In the second Delphi round, a consensus was reached on 73% of the items. No consensus was reached on 17 items. Conclusions The findings on practitioners' attitudes and priorities have relevant implications for subsequent DMHI development, dissemination, and implementation strategies, indicating that the highest-rated factors should be highlighted in the process.